DNA metabarcoding unveils authenticity and adulteration in commercial Chinese polyherbal preparations: Renshen Jianpi Wan as a critical case study - Zhou, Shilin; Zhou, Ting; Zhang, Yanmei; Yang, Bingqian; Niu, Junmei; Li, Weixian; Weitu, Yiyi; Long, Faming; Liu, Zhenwen; Zhou, Jing (Frontiers in Pharmacology, 2025)
ObjectivesEnsuring quality and authenticity of traditional medicines is crucial, particularly for multi-ingredient formulations like commercial Chinese polyherbal preparations (CCPPs). This study aims to authenticate Renshen Jianpi Wan (RSJPW), a classical CCPP composed of 11 prescribed botanical drugs, using DNA metabarcoding to overcome challenges in species-level identification of processed biological ingredients.MethodsWe analyzed 56 commercial RSJPW products from different manufacturers and production batches, alongside eight laboratory-prepared reference samples serving as authentic controls. A dual-marker protocol combining ITS2 and psbA-trnH regions was employed, with optimized DNA extraction and PCR protocols to mitigate degradation issues.ResultsDetection rates varied across samples, with the highest detection being 10 out of 11 prescribed ingredients in a single sample. The key fungal ingredient Poria cocos (茯苓) was consistently undetectable, likely due to DNA degradation during processing and challenges in extracting fungal DNA from complex matrices. Multiple high-abundance non-prescribed species from Fabaceae, Apiaceae, Brassicaceae, and other families were frequently detected as potential contaminants.ConclusionsThis study establishes a systematic framework for molecular authentication of complex herbal formulations, providing technical support for reliable identification of botanical drugs. While DNA metabarcoding offers valuable insights into CCPP composition, authentication of heavily processed ingredients remains a significant technical limitation. The integration with complementary analytical methods such as metabolomics could provide more comprehensive quality assessment in future studies, demonstrating the necessity of multi-analytical approaches in ensuring the authenticity of traditional medicine.